Pupil Selection and Enrolment in Comprehensive Schools in Urban Finland - Seppänen Piia; Pasu Terhi; Kosunen Sonja (Springer, 2025)
There is a pervasive myth that education policy for comprehensive schooling in Finland is non-selective, meaning that all children attend similar schools (peruskoulu) catering for the children who live nearby. Following from this is the idea that the Finnish education system must be relatively uniform and fair, since there is no obvious ability-grouping by tracks or streams for pupils under the age of 15. In this chapter we challenge these claims by analysing the ways in which public comprehensive schools select and track their pupils through different admission criteria for different teaching classes within schools. We argue that schools’ selection of pupils and the enrolment policies of cities vary nationally in a way that raises questions about the opportunities of attending ‘one school for all’. Our results indicate that selection processes for admission to emphasised teaching classes are fierce with schools not just evaluating pupil’s aptitudes for certain subjects but applying numerous criteria when enrolling pupils to emphasised teaching. Ways of testing, and the means by which they include and exclude pupils, may include aspects which reproduce existing social and economic inequalities in comprehensive schools.
Finland’s Famous Education System : Unvarnished Insights into Finnish Schooling